Promotion on Instagram and Institution Image on Course Decisions through Course Interest with Perceived Value as Moderator Variable (Study on Course Institution Students in the “Kampung Inggris”Area of Pare Kediri) - Braem Abraham Killa; Ery Tri Djatmika (CV. AFDIFAL MAJU BERKAH, 2022)
This study aims to determine how much influence promotion on Instagram and the image of the institution have on the decision to take a course through interest in taking a course with perceived value as a moderating variable. This research is a quantitative research using the software program SmartPLS version 3.2.9. The population in this study is a course institution in the “Kampung Inggris”of Pare, Kediri. The sample in this study were 385 respondents. The data was collected using a questionnaire, then the data was analyzed using descriptive statistical analysis and partial least squares (PLS). The results showed that: 1) Promotion on Instagram had a positive and significant effect on interest in taking courses. The value of the promotion variable on Instagram on interest in joining courses with a path coefficient of 0,031 and t statistic of 5.197 the value is greater than t table (1.960) or p ≤ 0,05; 2) The image of the institution has a positive and significant effect on interest in taking courses. The value of the institutional image variable on interest in attending the courses with a path coefficient of 0,605 and t statistic of 11.675 the value is greater than t table (1.960) or p ≤ 0,05; 3) Promotion on Instagram has a positive and significant effect on the decision to take a course. The value of the promotion variable on Instagram on the decision to take a courses with a path coefficient of 0,268 and t statistic of 5.753 the value is greater than t table (1.960) or p ≤ 0,05; 4) The image of the institution has a positive and significant effect on the decision to take the course. The value of the institutional image variable on the decision to take the courses with a path coefficient of 0,166 and t statistic of 2.810 the value is greater than t table (1.960) or p ≤ 0,05; 5) Interest in attending the course has a positive and significant effect on the decision to take the course. The value of the variable interest in attending on the decision to take the courses with a path coefficient of 0,215 and t statistic of 4.041 the value is greater than t table (1.960) or p ≤ 0,05; 6) Promotion on Instagram has a positive and significant indirect effect on decisions to take courses with interest in taking courses. Promotion on Instagram towards the decision to take a course through course interest in 0,065 and the t statistic of 2.931 the value is greater than t table (1.960) or ≤ 0,05; 7) Perceived value has a positive and significant effect on the decision to take the course. Perceived value has an influence on the decision to take the course with a path coefficient of 0.327 and a t statistic of 6.633 which is greater than t table (1.960) and a significance or p <0.05; 8) The image of the institution has a positive and significant indirect effect on the decision to take a course with an interest in attending the course. the influence of the institution's image on the decision to take a course through course interest is 0.130 and the t statistic is 4.052, the value is greater than t table (1.960) or p ≤ 0.05; 9) Perceived value positively moderates the influence of Promotions on Instagram on the decision to take courses. Perceived value has an influence in moderating promotions on Instagram on the decision to take a course with a path coefficient of 0.153 and a t statistic of 2.951 which is greater than t table (1.960) and a significance or p < 0.05; 10) Perceived value positively moderates the effect of interest in attending the course on the decision to take the course. Perceived value has an influence in moderating interest in attending a course on the decision to take a course with a path coefficient of 0.122 and a t statistic of 1.783 greater than t table (1.960) and significance or p < 0.05; 11) Perceived value positively moderates the influence of the institution's image on the decision to take the course. Perceived value has an influence in moderating the image of the institution on the decision to take the course with a path coefficient of -0.156 and a t statistic of 2.552 greater than t table (1.960) and significance or p < 0.05. Based on the results of the research above, suggestions can be given, namely to deepen and expand this research, both in terms of variables and research methods.